2018
DOI: 10.1038/s41598-018-34095-2
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Dolphin Distribution to Inform Future Spatial Conservation Decisions in a Marine Protected Area

Abstract: As marine predators experience increasing anthropogenic pressures, there is an urgent need to understand their distribution and their drivers to inform spatial conservation planning. We used an ensemble modelling approach to investigate the spatio-temporal distribution of southern Australian bottlenose dolphins (Tursiops cf. australis) in relation to a variety of ecogeographical and anthropogenic variables in Coffin Bay, Thorny Passage Marine Park, South Australia. Further, we evaluated the overlap between cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 97 publications
1
57
0
Order By: Relevance
“…Important human disturbances include direct (bycatch) and indirect (prey depletion) impacts from fisheries (Reeves et al, 2013), as well as physical and acoustic disturbance mainly by marine traffic (Pennino et al, 2017;Erbe et al, 2019), seismic activities from oil and gas exploration and naval sonars (Rosenbaum and Collins, 2006;Henderson et al, 2014), and various sources of pollution (Tanabe, 2002;Allen et al, 2011;Venn-Watson et al, 2015). Increasing anthropogenic stressors include coastal-offshore development and energy production, resource extraction, tourism, and climate change (MacLeod, 2009;Passadore et al, 2018b). To assess the potential impact from these human threats, baseline information on cetacean occurrence at a local level is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Important human disturbances include direct (bycatch) and indirect (prey depletion) impacts from fisheries (Reeves et al, 2013), as well as physical and acoustic disturbance mainly by marine traffic (Pennino et al, 2017;Erbe et al, 2019), seismic activities from oil and gas exploration and naval sonars (Rosenbaum and Collins, 2006;Henderson et al, 2014), and various sources of pollution (Tanabe, 2002;Allen et al, 2011;Venn-Watson et al, 2015). Increasing anthropogenic stressors include coastal-offshore development and energy production, resource extraction, tourism, and climate change (MacLeod, 2009;Passadore et al, 2018b). To assess the potential impact from these human threats, baseline information on cetacean occurrence at a local level is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with what Ilangakoon and Sathasivam (2012) suggested that blue whales can be present in relatively small, localized highly productive feeding areas associated with strong upwelling year-round in Sri Lanka, and only make localized movements within this area. O. brevirostris prefers shallow, sheltered estuaries, such as in the NEBS, since such areas are commonly highly productive systems that can attract fish and top predators (Passadore et al, 2018). It has been shown before that distinct isobaths (-200m and -1000m) are important factors in determining the distribution of many cetaceans known to forage on pelagic schooling fish or deep-water prey (Goetz et al, 2015;Scales et al, 2014).…”
Section: Topographic Complexity Indicating High Habitat and Prey Divementioning
confidence: 99%
“…Cetaceans are particularly susceptible to human threats because of their life-history traits i.e. late maturity and low reproductive rate (Passadore et al, 2018). The variety of anthropogenic pressures includes interactions with fisheries (entanglement, bycatch, prey depletion) (Read, 2008;Reeves et al, 2013), physical and acoustic disturbance mainly by marine traffic (ship strikes, underwater noise) (Erbe et al, 2019;Pennino et al, 2017), seismic activities from oil and gas exploration and naval sonars (Henderson et al, 2014;Rosenbaum and Collins, 2006), and pollution (oil spills, plastic debris, heavy metals, and other chemicals) (Allen et al, 2011;Monk et al, 2014;Tanabe, 2002;Venn-Watson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important human disturbances include direct (bycatch) and indirect (prey depletion) impacts from fisheries (Reeves et al, 2013), as well as physical and acoustic disturbance mainly by marine traffic (Erbe et al, 2019;Pennino et al, 2017), seismic activities from oil and gas exploration and naval sonars (Henderson et al, 2014;Rosenbaum and Collins, 2006), and various sources of pollution (Allen et al, 2011;Tanabe, 2002;Venn-Watson et al, 2015). Increasing anthropogenic stressors include coastaloffshore development and energy production, resource extraction, tourism, and climate change (MacLeod, 2009;Passadore et al, 2018b). To assess the potential impact from these human threats, baseline information on cetacean occurrence at a local level is urgently needed.…”
Section: Introductionmentioning
confidence: 99%